Magnesium sulphate improves pulmonary function after video-assisted thoracoscopic surgery: A randomised double-blind placebo-controlled study. Issue 8 (August 2017) - Sohn, Hye-Min; Jheon, Sang-Hoon; Nam, Sunwoo; Do, Sang-Hwan
Abstract : BACKGROUND: Reduced lung volumes are unavoidable after lung resection surgery. Magnesium sulphate (MgSO4 ) administration has been reported to reduce the requirement for neuromuscular blocking drugs and postoperative analgesics in surgical patients. OBJECTIVE: To investigate the effect of MgSO4 on pulmonary function after video-assisted thoracoscopic surgery (VATS). DESIGN: A randomised, double-blind, placebo-controlled trial. SETTING: A university tertiary care centre. PATIENTS: Sixty-six patients scheduled for pulmonary lobectomy or segmentectomy via VATS. INTERVENTION: Patients were allocated to one of two groups: the Mg (MgSO4 50 mg kg −1 intravenously for 10 min, followed by a continuous infusion of 15 mg kg −1 h −1 during surgery) or the control (same volume of 0.9% saline). MAIN OUTCOME MEASURES: Pulmonary function tests [forced expiratory volume in 1 s (FEV1 ), forced vital capacity (FVC) and peak expiratory flow rate] were measured before surgery and at three time points after surgery (2, 24 and 48 h postoperatively) using a portable spirometer. Twelve months after surgery, pulmonary function test values were repeated at a regular outpatient follow-up visit. RESULTS: FEV1 at 24 (1.7 ± 0.6 vs. 1.3 ± 0.5 l, P = 0.033) and 48 h (1.7 ± 0.6 vs. 1.4 ± 0.5 l, P = 0.021) and FVC at 24 (2.0 ± 0.8 vs. 1.6 ± 0.6 l, P = 0.038) and 48 h (2.2 ± 0.8 vs. 1.7 ± 0.7 l, P = 0.008) after surgery were significantly greater in the Mg group. Patients in the Mg group required less rocuronium than those in the control group (64.2 ± 19.9 vs. 74.9 ± 20.3 mg, respectively; P = 0.041). Consumption of postoperative patient-controlled analgesia was also significantly less at 24 and 48 h after surgery in the Mg group ( P = 0.022 and 0.015, respectively), although pain scores and rescue analgesics were comparable. Five patients in the control group were diagnosed with postoperative pneumonia using clinical and radiological criteria before discharge. FEV1 and FVC at 12 months after surgery were not different between the two groups. CONCLUSION: Intraoperative administration of MgSO4 improved pulmonary function and reduced the need for rocuronium and postoperative analgesics in patients who underwent VATS. TRIAL REGISTRATION: cris.nih.go.kr identifier: KCT0001410